Dental caries and related factors in Brazilian children from fluoridated and non-fluoridated areas - Parisotto, Thaís Manzano; Fernandes, Luciana Maria P. Da S. R.; Carvalho, Fabíola Galbiatti De; Coelho, Eliete De Oliveira; Nobre-dos-santos, Marinês; Oliveira, Olga Maria M. De Faria; Sponchiado, Sandra Regina Pombeiro [UNESP] (Pontifícia Universidade Católica do Rio Grande do Sul, 2010)
PURPOSE: To compare the caries prevalence, saliva buffering capacity (SBC), oral hygiene (OH), dietary habits, family income (FI) and frequency of visits to a dental office (Do) between Brazilian children living in areas with and without fluoridated public water supply. METHODS: Forty-six 5-7-year-old preschoolers were selected in Itatiba, SP, Brazil; 19 were from a fluoridated area, and 27 were from a non-fluoridated area. The caries index was determined according to the World Health Organization criteria, and the SBC was assessed by titration with hydrochloric acid. The FI, frequency of OH and visits to Do were estimated by questionnaire. The dietary habits were assessed with a diet chart. The differences between the groups were analyzed with Mann-Whitney-U tests (α=0.05). RESULTS: Children from the non-fluoridated area showed significantly higher dmft/DMFT than those from the fluoridated area, but they showed significantly lower SBC, OH frequency and FI. No significant differences were observed between the areas for dietary habits and visits to Do. CONCLUSION: Children from fluoridated areas showed higher salivary buffering capacity, family income and oral hygiene frequency as well as lower caries prevalence, supporting the beneficial effect of fluoride in the tap water for caries prevention.

OBJETIVO: Comparar prevalência de cárie, capacidade tamponante da saliva (CTS), higiene bucal (HB), hábitos dietéticos, renda familiar (RF) e frequência de visita a consultórios odontológicos (Co) entre crianças brasileiras residentes em áreas de água de abastecimento público fluoretadas e não fluoretadas. METODOLOGIA: Quarenta e seis crianças entre 5-7 anos foram selecionadas em Itatiba-SP-Brasil, sendo 19 pertencentes à área fluoretada e 27 à área não fluoretada. O índice de cárie foi determinado de acordo com o critério da Organização Mundial de Saúde e a CTS foi medida por titulação com ácido clorídrico. A RF, frequência de HB e visita ao Co foram estimadas por questionário. Os hábitos dietéticos foram avaliados com diário de dieta. As diferenças entre as variáveis foram analisadas pelo teste de Mann Whitney (α=0,05). RESULTADOS: As crianças da área não fluoretada apresentaram significativamente maior ceod/CPOD que àquelas da área fluoretada, porém significativamente menor CTS, HB e RF. Com relação a hábitos dietéticos e visitas ao Co, não foi observada diferença significativa entre as áreas. CONCLUSÃO: As crianças da área fluoretada apresentaram maior capacidade tamponante da saliva, renda familiar e frequência de higiene bucal, assim como menor prevalência de cárie, reforçando o efeito benéfico do flúor nas águas de abastecimento para prevenir a cárie.
Cárie dentária e fatores relacionados em crianças Brasileiras de região com água fluoretada e não fluoretada
Keywords: Dental caries; fluoride; diet; saliva; buffers; Cárie dentária; flúor; dieta; saliva; tampão